Compulsive buying behavior among workers in PDT Jelebu and Naza Sdn. Bhd. / Noramarina Selamat and Nur Asikin Redzwan - Selamat, Noramarina; Redzwan, Nur Asikin (Faculty of Business and Management, 2015)
This research conducted focusing on the factors influencing compulsive buying among Pejabat Daerah dan Tanah (PDT) Jelebu and Naza Sdn. Bhd. This study identifies three independent variables which are peoples’ impression, financial satisfaction, and financial literacy. In line with this, the main objectives of this study are (1) to examine the factors that influence the compulsive buying habits among PDT Jelebu and Naza Sdn. Bhd. (2) to investigate the relationship between peoples’ impression, financial satisfaction and financial literacy with compulsive buying. The respondent of this study was the employees of PDT Jelebu and Naza Sdn. Bhd. 240 questionnaires had been distributed equally to both companies. The researchers had used convenient sampling as a sampling technique. The process of analyzing and interpreting data is collected. The results from the model used are correlation and regression analysis shown that there is a significant relationship between peoples’ impression and financial satisfaction with compulsive buying. The researchers also have come out with a few recommendations to be taken into consideration. By implementing these recommendations, it will help the future researcher to investigate more factors that get affect compulsive buying.